2002
DOI: 10.2134/jeq2002.1214
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry Practices, Runoff, and Nutrient Loss

Abstract: A paired watershed study consisting of agroforestry (trees plus grass buffer strips), contour strips (grass buffer strips), and control treatments with a corn (Zea mays L.)-soybean [Glycine max (L.) Merr.] rotation was used to examine treatment effects on runoff, sediment, and nutrient losses. During the (1991-1997) calibration and subsequent three-year treatment periods, runoff was measured in 0.91- and 1.37-m H-flumes with bubbler flow meters. Composite samples were analyzed for sediment, total phosphorus (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(158 citation statements)
references
References 24 publications
4
149
0
4
Order By: Relevance
“…1), i.e., West (3.16 ha), Center (4.44 ha), and East (1.54 ha), located in Knox County, Missouri, at the University of Missouri Greenley Memorial Research Center (40° 1′ N, 92° 11′ W) (Udawatta et al, 2002. Slopes within the watersheds ranged from 0% to 6%.…”
Section: Site Description and Monitoring Datamentioning
confidence: 99%
See 1 more Smart Citation
“…1), i.e., West (3.16 ha), Center (4.44 ha), and East (1.54 ha), located in Knox County, Missouri, at the University of Missouri Greenley Memorial Research Center (40° 1′ N, 92° 11′ W) (Udawatta et al, 2002. Slopes within the watersheds ranged from 0% to 6%.…”
Section: Site Description and Monitoring Datamentioning
confidence: 99%
“…The numbers of sediment and TP data available for each watershed varied and are provided in table 2. Other details not included in this summary of the research methods for the 16-year data collection period can be found in Udawatta et al (2002Udawatta et al ( , 2004Udawatta et al ( , 2011.…”
Section: Site Description and Monitoring Datamentioning
confidence: 99%
“…Soil quality is improved by increased levels of organic matter, more diverse microbial populations, and improved nutrient cycling, which may increase crop productivity and the ability to cope with drought [65,86,87]. The water quality benefits occur as non-point source pollution from row crops is reduced by incorporating agroforestry vegetative buffer strips [88][89][90]. On a "paired" watershed study in Missouri, agroforestry and grass buffer strips reduced phosphorus and nitrogen loss from a corn-soybean rotation [88].…”
Section: Benefits Of Agroforestrymentioning
confidence: 99%
“…The highest levels of organic matter were observed at the upstream stations, where riparian quality was also highest (higher percentage of forest, and higher QBR values) and leaf litter represents an important local source of organic matter (Udawatta et al 2002;Webster et al 1999). Levels of organic matter were lower at station 2 possibly related to the lower levels of forest land use compared to the upper stations.…”
Section: Discussionmentioning
confidence: 92%